The Phenomenon of Longing and Nostalgia in the Poetry of Zamakhshari (d. 538), an Analytical Study - Rabei , Amer Mahmood (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to shed light on the concepts of longing and nostalgia present in Zamakhshari’s poetry and to explore the underlying psychological motivations. Methods: The study was conducted through observation and analysis of representative texts to achieve the outlined objectives. Results: The study findings suggest that Al-Zamakhshari utilized the technique of personification to establish psychological distance, exemplified by feelings of empathy and love, and aesthetic distance, manifested through avoidance of direct expression. Owing to certain economic and social circumstances, Al-Zamakhshari was compelled to depart from his native Zamakhshar and reside in Khwarazm or places like Baghdad in pursuit of knowledge and education for a period of time. Nonetheless, he continually experienced a strong yearning for his homeland. The study revealed another reason why the poet distanced himself from his homeland and birthplace, which was his intention to visit the holy land of Mecca, where he had significant experiences and memories in the sacred Kaaba and other holy landmarks. The study also indicates that Al-Zamakhshari was influenced by ancient poets, both in terms of imagery and meanings. His poetry, particularly those dedicated to the places that captivated his thoughts and soul, was marked by elegance, melancholy, sadness, and genuine emotion. Conclusion: Zamakhshari’s employment of personification and metaphorical thinking techniques was driven both by a technical necessity to animate inanimate objects and abstract concepts, making his depicted images and scenes more potent and impactful to the readers, as well as a psychological need for closeness and serenity. His influence by ancient poets is predictable, as a new text is a mosaic of the preceding texts that shape it. The study recommends examining other stylistic features in Zamakhshari’s poetry, such as intertextuality and personification of place.